ERCC1 SNPs as Potential Predictive Biomarkers in Non-Small Cell Lung Cancer Patients Treated With Platinum-Based Chemotherapy. (21st April 2015) - Kalikaki, Aristea; Voutsina, Alexandra; Koutsopoulos, Anastasios; Papadaki, Chara; Sfakianaki, Maria; Yachnakis, Emmanouel; Xyrafas, Alexandros; Kotsakis, Athanasios; Agelaki, Sofia; Souglakos, John; Mavroudis, Dimitrios; Georgoulias, Vassilis
<x xml:space="preserve">Abstract</x> Polymorphisms in ERCC1, XPD, and XRCC1 were examined for (a) association with the clinical outcome of 107 non-small cell lung cancer patients receiving front-line platinum-based chemotherapy, and (b) correlation with the ERCC1 mRNA levels of 176 chemo-naive primary tumors. The ERCC1-C8092 allele and the number of ERCC1 polymorphic variants (C8092A and Asn118Asn) were associated with progression-free survival. In non-squamous histology, tumoral ERCC1 mRNA levels were lower in patients homozygous for ERCC1-C8092 as compared with the patients carrying the A allele (p = .024). These findings merit investigation in larger cohorts of patients treated with uniform regimens.